Changing the landscape for type 1 diabetes: the first step to prevention. Issue 10205 (5th October 2019) - Dayan, Colin M; Korah, Maria; Tatovic, Danijela; Bundy, Brian N; Herold, Kevan C
Summary: Over several decades, studies have described the progression of autoimmune diabetes, from the first appearance of autoantibodies until, and after, the diagnosis of clinical disease with hyperglycaemia and insulin dependence. Despite the improved management of type 1 diabetes with exogenous insulin, most patients do not meet clinical glycaemic goals, and diabetes remains an important medical problem that affects children and adults. Clinical and preclinical studies have suggested strategies to prevent the diagnosis of type 1 diabetes in people at risk, but the outcomes of previous clinical trials have not met their primary endpoints of disease prevention or delay. The results from the TN-10 teplizumab prevention trial show that the diagnosis of type 1 diabetes can be delayed by treatment with a FcR non-binding monoclonal antibody to CD3 in people at high risk for disease. This Series paper discusses how this clinical achievement raises new questions about for whom, and when, immunological strategies might be developed to prevent type 1 diabetes, and how to achieve this goal.